How can we compute the series $\displaystyle \sum_{n\geq 1}\frac{(-1)^n \ln n}{n}$?

I know it is $\eta '(1)$ , where $\eta$ is the $\eta$ Dirichlet Function , i know its value. But I don't know how to compute it.

An approach I tried is to expand the series, then gather together the odd and the even terms , use $\zeta$ (Riemann's function) and that's all. Then no idea.

Any ideas are welcome.

  • $\begingroup$ I want to compute it... meaning I want to get the result wikipedia says. $\endgroup$ – Tolaso Sep 16 '14 at 18:43
  • $\begingroup$ What does Wikipedia say it is? $\endgroup$ – robjohn Sep 16 '14 at 23:37
  • $\begingroup$ It gives the result $\gamma \ln 2- \dfrac{\ln^2 2}{2}$. $\endgroup$ – Tolaso Sep 17 '14 at 7:32
  • $\begingroup$ Here's a link of sos440's blog article. I think it is quite nice. $\endgroup$ – karvens Sep 27 '14 at 7:24

This is given in equation $(8)$ of this answer using the Euler-Maclaurin Sum Formula, which says that $$ \sum_{k=1}^n\frac{\log(k)}{k}=C+\frac{\log(n)^2}{2}+O\left(\frac{\log(n)}{n}\right)\tag{1} $$ for some constant $C$, and that $$ \sum_{k=1}^n\frac1{k}=\log(n)+\gamma+O\left(\frac1n\right)\tag{2} $$ Note that $$ \begin{align} \sum_{k=1}^{2n}(-1)^k\frac{\log(k)}{k} &=2\sum_{k=1}^{n}\frac{\log(2k)}{2k} -\sum_{k=1}^{2n}\frac{\log(k)}{k}\\ &=\sum_{k=1}^{n}\frac{\log(k)}{k}+\log(2)\sum_{k=1}^{n}\frac1{k} -\sum_{k=1}^{2n}\frac{\log(k)}{k}\\ &=C+\frac{\log(n)^2}{2}+O\left(\frac{\log(n)}{n}\right)\\ &+\log(2)\left(\log(n)+\gamma+O\left(\frac1n\right)\right)\\ &-C-\frac{\log(2n)^2}{2}-O\left(\frac{\log(2n)}{2n}\right)\\ &=\gamma\log(2)-\frac{\log(2)^2}{2}+O\left(\frac{\log(n)}{n}\right)\tag{3} \end{align} $$ Let $n\to\infty$ in $(3)$ and we get $$ \sum_{k=1}^\infty(-1)^k\frac{\log(k)}{k}=\gamma\log(2)-\frac{\log(2)^2}{2}\tag{4} $$ Note that it doesn't matter what the constant $C$ is, as it gets cancelled out of the calculations.

  • $\begingroup$ Nice answer! +1. $\endgroup$ – Olivier Oloa Sep 17 '14 at 5:38
  • $\begingroup$ @robjohn very nice answer! $\endgroup$ – Tolaso Sep 17 '14 at 7:33

Let $s>1$. Observe that $$\displaystyle \sum_{n\geq 1}\frac{(-1)^n }{n^s}=\frac{1}{2^s}\sum_{n\geq 1}\frac{1}{n^s}-\sum_{n\geq 0}\frac{1}{(2n+1)^s}\tag1$$ and $$\displaystyle \sum_{n\geq 1}\frac{1}{n^s}=\frac{1}{2^s}\sum_{n\geq 1}\frac{1}{n^s}+\sum_{n\geq 0}\frac{1}{(2n+1)^s}\tag2$$ then $(1)$ + $(2)$ gives $$\displaystyle \sum_{n\geq 1}\frac{(-1)^n }{n^s}=\left(\frac{1}{2^{s-1}}-1\right)\sum_{n\geq 1}\frac{1}{n^s}=\left(\frac{1}{2^{s-1}}-1\right)\zeta(s)\tag3$$ where $\zeta(\cdot)$ is the Riemann zeta function.

Now differentiating $(3)$ with respect to $s$ gives $$\displaystyle -\sum_{n\geq 1}\frac{(-1)^n \ln n}{n^s}=\left(-\frac{\ln 2}{2^{s-1}}\right)\zeta(s)+\left(\frac{1}{2^{s-1}}-1\right)\zeta'(s)\tag4$$ and letting $s$ tend to $1^+$, gives the result:

$$\displaystyle \sum_{n\geq 1}\frac{(-1)^n }{n}\ln n=-\frac{\ln^2 2}{2}+\gamma \ln 2\tag5$$

where $\gamma$ is the Euler constant and where, near $s=1^+$, we have used $$\frac{1}{2^{s-1}}= 1- (s-1)\ln 2+(s-1)^2\frac{\ln^2 2}{2}+\mathcal{O}((s-1)^3)$$ together with the Laurent series expansions $$ \begin{align} \zeta(s) &=\frac{1}{s-1}+\gamma+\mathcal{O}(s-1)\\\\ \zeta'(s)&=-\frac{1}{(s-1)^2}+\mathcal{O}(1).\end{align}$$

  • $\begingroup$ The argument in my answer is from an answer to a question that asked why $\gamma$ is the constant term in the Laurent expansion of $\zeta(s)$. We can use that answer to justify the Laurent expansion of $\zeta(s)$ here. $\endgroup$ – robjohn Sep 16 '14 at 23:28
  • $\begingroup$ I believe, however, that the answer should be $\gamma\log(2)-\frac{\log(2)^2}{2}$ $\endgroup$ – robjohn Sep 16 '14 at 23:39
  • $\begingroup$ @robjohn Typo fixed. Thanks! Yes, in this answer, I considered the Laurent expansion for $\zeta(s)$ as a known fact. $\endgroup$ – Olivier Oloa Sep 17 '14 at 5:37

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.